Penentuan Kadar Kalium Sorbat dan Persen Recovery Pada Selai dengan Metoda High Performance Liquid Chromatography - Pevi Riani; Ulvie Ameinda Fannin (REACTOR: Journal of Research on Chemistry and Engineering, 2020)
Fruit jam is one of the preserved products that have a soft texture that contains crushed fruit and is mixed with sugar with the addition or without the addition of water. Preservatives are added to prevent damage to jams. A preservative that is usually added to jam is potassium sorbate. Potassium sorbate is commonly used as a preservative because it dissolves more easily when added to food. This study aims to determine the levels of potassium sorbate in jam samples. Potassium sorbate was determined using High Performance Liquid Chromatography (HPLC). From the test results, it was found that potassium sorbate levels ranged from719, 65 mg/kg to 757,24 mg/kg. The results of this test will be compared with the standards set by the Food and Drug Supervisory Agency (BPOM) No. 36 of 2013 concerning the maximum limit for the use of preservative food additives, namely 500 mg/kg. From the test results, it can be seen that the potassium sorbate in all samples exceeds the quality standard set by the BPOM. Therefore, people must be more careful in choosing jam to consume daily. The test results have used the right method, namely by adjusting the stationary phase, mobile phase and the right wavelength so that the% recovery results are 103%.